challenge question -- Factor the polynomial completely

lookagain

Elite Member
Joined
Aug 22, 2010
Messages
3,255
Edit:

Demonstrate at least two methods for factoring the following polynomial
completely over the integers.


x5+x4+x3+x2+x+1\displaystyle x^5 + x^4 + x^3 + x^2 + x + 1
 
Last edited:
Method 1:

Factor first by grouping:

(x5+x4)+(x3+x2)+(x+1)=x4(x+1)+x2(x+1)+(x+1)=(x+1)(x4+x2+1)\displaystyle (x^5+x^4)+(x^3+x^2)+(x+1)=x^4(x+1)+x^2(x+1)+(x+1)=(x+1)(x^4+x^2+1)

Now, for the quartic factor assume it may be factored as follows:

x4+x2+1=(x2+ax+1)(x2+bx+1)=x4+(a+b)x3+(ab+2)x2+(a+b)x+1\displaystyle x^4+x^2+1=(x^2+ax+1)(x^2+bx+1)=x^4+(a+b)x^3+(ab+2)x^2+(a+b)x+1

Equating coefficients, we find:

a+b=0\displaystyle a+b=0

ab+2=1\displaystyle ab+2=1

and so one solution is (a,b)=(1,1)\displaystyle (a,b)=(1,-1) and we have:

x4+x2+1=(x2+x+1)(x2x+1)\displaystyle x^4+x^2+1=(x^2+x+1)(x^2-x+1) which means:

x5+x4+x3+x2+x+1=(x+1)(x2+x+1)(x2x+1)\displaystyle x^5+x^4+x^3+x^2+x+1=(x+1)(x^2+x+1)(x^2-x+1)

Method 2:

Let:

S=x5+x4+x3+x2+x+1\displaystyle S=x^5+x^4+x^3+x^2+x+1 and so:

Sx=x6+x5+x4+x3+x2+x=S+x61\displaystyle Sx=x^6+x^5+x^4+x^3+x^2+x=S+x^6-1 hence:

S(x1)=x61=(x3+1)(x31)=(x+1)(x2x+1)(x1)(x2+x+1)\displaystyle S(x-1)=x^6-1=(x^3+1)(x^3-1)=(x+1)(x^2-x+1)(x-1)(x^2+x+1) thus:

S=(x+1)(x2x+1)(x2+x+1)\displaystyle S=(x+1)(x^2-x+1)(x^2+x+1)
 
A) Give the completely factored form over the integers of the following polynomial, and

B) demonstrate at least two methods for doing so.


x5+x4+x3+x2+x+1\displaystyle x^5 + x^4 + x^3 + x^2 + x + 1


(x+1)(x4+x2+1) → (x+1)(x4+2x2+1 - x2) → (x+1)(x2+1+x)(x2+1-x)

or

(x3+1)(x2+x+1) →(x+1)(x2-x+1)(x2+x+1)
 
Here is another:


(x^5 + 1) + (x^4 + x^3 + x^2 + x) =

(x + 1)(x^4 - x^3 + x^2 - x + 1) + (x^4 + x^3) + (x^2 + x) =

(x + 1)(x^4 - x^3 + x^2 - x + 1) + x^3(x + 1) + x(x + 1) =

(x + 1)(x^4 - x^3 + x^2 - x + 1 + x^3 + x) =

(x + 1)(x^4 + x^2 + 1) =



(You can continue simplifying this with one of the above steps in
any of the appropriate above posts.)
 
Last edited:
Here's another way.

Since x5+x4+x3+x2+x+1=x61x1\displaystyle x^5+x^4+x^3+x^2+x+1 = \dfrac{x^6-1}{x-1} the roots of this polynomial are exactly the set {zC{1}  ;  z6=1}\displaystyle \{z\in \mathbb{C}-\{1\}\,\,;\,\, z^6=1\}, i.e. the roots of unity, ignoring the positive real root. They are e±iπ/3,e±i2π/3,1\displaystyle e^{\pm i\pi/3},e^{\pm i2\pi/3}, -1 .

We want a real factorization obviously, and we can see that the conjugate pair to each root is present (as it should be). Pairing them off we get the (minimal) polynomials for each:

(xeiπ/3)(xeiπ/3)=x2x+1\displaystyle (x-e^{i\pi/3})(x-e^{- i\pi/3}) = x^2-x+1
(xei2π/3)(xei2π/3)=x2+x+1\displaystyle (x-e^{i2\pi/3})(x-e^{- i2\pi/3}) = x^2+x+1
x(1)=x+1\displaystyle x-(-1) = x+1

There is an abstract algebra/number theoretic variation of the above that can be performed for the general case too.
 
Hello, lookagain

This is a variation of daon's solution.


Demonstrate at least two methods for factoring the following polynomial:

. . . P(x)  =  x5+x4+x3+x2+x+1\displaystyle P(x) \;=\;x^5 + x^4 + x^3 + x^2 + x + 1

P(x)  =  x61x1  =  (x3)2(12)diff. of squaresx1\displaystyle P(x) \;=\;\dfrac{x^6 - 1}{x-1} \;=\;\dfrac{\overbrace{(x^3)^2 - (1^2)}^{\text{diff. of squares}}}{x-1}

. . . . .=  (x31)diff.of cubes(x3+1)sum of cubesx1\displaystyle =\;\dfrac{\overbrace{(x^3-1)}^{\text{diff.of cubes}}\cdot\overbrace{(x^3+1)}^{\text{sum of cubes}}}{x-1}

. . . . .=  (/////x1)(x2+x+1)(x+1)(x2x+1)/////x1\displaystyle =\; \dfrac{(\color{red}{\rlap{/////}}{x-1})(x^2+x+1)(x+1)(x^2-x+1)}{\color{red}{\rlap{/////}}x-1}

. . . . .=  (x+1)(x2+x+1)(x2x+1)\displaystyle =\; (x+1)(x^2+x+1)(x^2-x+1)
 
Hello, lookagain

This is a variation of daon's solution.



P(x)  =  x61x1  =  (x3)2(12)diff. of squaresx1\displaystyle P(x) \;=\;\dfrac{x^6 - 1}{x-1} \;=\;\dfrac{\overbrace{(x^3)^2 - (1^2)}^{\text{diff. of squares}}}{x-1}

. . . . .=  (x31)diff.of cubes(x3+1)sum of cubesx1\displaystyle =\;\dfrac{\overbrace{(x^3-1)}^{\text{diff.of cubes}}\cdot\overbrace{(x^3+1)}^{\text{sum of cubes}}}{x-1}

. . . . .=  (/////x1)(x2+x+1)(x+1)(x2x+1)/////x1\displaystyle =\; \dfrac{(\color{red}{\rlap{/////}}{x-1})(x^2+x+1)(x+1)(x^2-x+1)}{\color{red}{\rlap{/////}}x-1}

. . . . .=  (x+1)(x2+x+1)(x2x+1)\displaystyle =\; (x+1)(x^2+x+1)(x^2-x+1)

MarkFL said:
Method 2:

Let:

S=x5+x4+x3+x2+x+1\displaystyle S=x^5+x^4+x^3+x^2+x+1 and so:

Sx=x6+x5+x4+x3+x2+x=S+x61\displaystyle Sx=x^6+x^5+x^4+x^3+x^2+x=S+x^6-1 hence:

S(x1)=x61=(x3+1)(x31)=(x+1)(x2x+1)(x1)(x2+x+1)\displaystyle S(x-1)=x^6-1=(x^3+1)(x^3-1)=(x+1)(x^2-x+1)(x-1)(x^2+x+1) thus:

S=(x+1)(x2x+1)(x2+x+1)\displaystyle S=(x+1)(x^2-x+1)(x^2+x+1)


These two (MarkFL's and soroban's versions) look essentially the same to me.


- - - - - - - - - - - - - - - - -


Others:


(x^5 + x^2) + (x^4 + x) + (x^3 + 1) =

x^2(x^3 + 1) + x(x^3 + 1) + 1(x^3 + 1) =

(x^3 + 1)(x^2 + x + 1) =

(x + 1)(x^2 - x + 1)(x^2 + x + 1)


. . . . . . . . . . . . . . . . . . . . .


(x^5 + x^3 + x) + (x^4 + x^2 + 1) =

x(x^4 + x^2 + 1) + 1(x^4 + x^2 + 1) =

(x^4 + x^2 + 1)(x + 1) =

(x^2 - x + 1)(x^2 + x + 1)(x + 1)
 
Top